Sergey Smbatyan conducts Rimsky-Korsakov's Scheherazade Armenian State Symphony Orchestra - Rimsky-Korsakov, Nikolai (Medici.tv, 2018)
The concert starts with Rimsky-Korsakov's four-movement symphonic suite Scheherazade, considered one of the best pieces of symphonic music in the world. It is interpreted by Maestro Sergey Smbatyan and the Armenian State Symphony Orchestra. Inspired by the fictional past of the Arabian fairytale collection A Thousand and One Nights, listeners are swept away to the world of the beautiful Scheherazade, who avoids execution by mesmerizing the Sultan of Baghdad for one-thousand-and-one nights with one-thousand-and-one tales. Photo: Sergey Smbatyan © SYOA.
Keywords: concert; Webcast; Internet videos; Vidéos sur Internet